THE EFFECTIVENESS OF THE LEAF EXTRACT OF LIME AND LEMON GRASS AS NATURAL MOSQUITO INSECTICIDE - Awan, Ilham; M. Ali Sodik; Maulina Nurikasari (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2018)
One of the prevention and eradication of mosquitoes that is safe to be used is natural ingredients from plants. Extract lime leaves and lemon grass contain compounds limonoida, sitronela, and geraniol which are toxic to mosquitoes. The purpose of this study was to determine differences in the effectiveness of extract of lime leaves and lemon grass as natural mosquito insecticide. This study used experimental research and the research method was posttest-only control design. It was an experimental design that consisted of two groups, each of which was selected randomly, namely the control group and the experimental group. The research sample number 5 mice per group with 6 repetitions. Bivariate data analysis using a paired t-test and multivariate data analysis using ANOVA test with α value = 0.05. The results showed that lime leaf extract (sig = 0.000) leaf extract, lemon grass (= 0.002), as well as extract mix lime leaves and lemongrass (sig = 0,000) were effective in killing adult mosquitoes. However, there was no significant difference in the number of adult mortality between minute 10 and minute 20 in the experimental group. The mixture of lime leaves and lemon grass extract were the most influential ingredients. It was effective against adult mortality levels. This extract contained compounds citronellal and geraniol twice to kill more mosquitoes.